THE EFFECTS OF SOME FACTORS ON IN VITRO BIOMASS PRODUCTION OF VIETNAMESE GINSENG PANAX VIETNAMENSIS HA ET GRUSHV.) AND PRELIMINARY ANALYSIS OF SAPONIN CONTENT - Nhựt, Dương Tấn (Vietnam Journal of Biotechnology, 2011)
" Panax vietnamensis Ha et Gmshv., a rare Panax genus of Vietnam, is a well known Vietnamese ginseng (Ngoc Linh Ginseng) for its rich pharmaceutical compositions, most importantly saponin. In order to obtain a stable and saponin-rich biomass of P. vietnamensis, a tissue culture procedure was established. A TLC analysis of saponin composition was also conducted to investigate the presence of saponin in callus, shoot and root biomass. Successful callus induction from leaf and petiole explants was obtained from MS medium n supplemented with 1.0 mg/l 2,4-D (2,4-dichlorophenoxyacetic acid), 0.2 mg/l TDZ (Thidiazuron) under a photoperiod of 16 h. In the following steps, the optimal auxin and its concenfration, appropriate photoperiod condition as well as callus size that were the best for callus proliferation were investigated. Among the auxins, including 2,4-D, IBA (Indole-3-butyric acid) and NAA (a-Naphthaleneacetic acid), 2,4-D at 1.0 mg/l was found to be the most effective for callus growth. Callus at the size of 0.5 x 0.5 cm grew the best as compared to bigger ones, such as 0.7 x 0.7 cm and 1.0 x 1.0 cm. The effects of phytohormones, sucrose and activated charcoal (AC) on shoot regeneration from callus and shoot proliferation have also been studied. Calli cultured on MS medium supplemented with 1.0 mg/l BA and 1.0 mg/l NAA regenerated more shoots. The suitable « medium for shoot proliferation was MS’/z medium, supplemented with 1.0 mg/l BA, 0.5 mg/l NAA, 50 g/l sucrose and 2.0 mg/l AC. Callus was grown on MS’/2 medium supplemented with 3.0 mg/l NAA to regenerate roots. Root proliferation was obtained on MS’A medium containing 5.0 mg/l NAA. In saponin analysis experiment, thin layer chromatograms show that obtained calli, shoots and roots from the above experiments had ginsenoside-Rgl and majonoside-R2, two main ginsenosides of Vietnamese Ginseng but only roots have ginsenoside-Rbl. These results indicate that Vietnamese Ginseng biomass can be used as a new source for saponin isolation for pharmaceutical and cosmetic industry.